Processes and patterns of glacier-influenced sedimentation and recent tidewater glacier dynamics in Darbel Bay, western Antarctic Peninsula - Batchelor, CL; Dowdeswell, JA; Hogan, KA; Larter, RD; Parsons, E; West, O (Cambridge University Press (CUP), 2019)
Abstract Bathymetric data of unprecedented resolution are used to provide insights into former ice dynamics and glacial processes in a western Antarctic Peninsula embayment. An assemblage of submarine glacial landforms, which includes subglacially produced streamlined features and ice-marginal ridges, reveals the former pattern of ice flow and retreat. A group of more than 250 small (< 1–3 m high, 10–20 m wide) and relatively evenly spaced recessional moraines was identified beyond the margin of Philippa Glacier. The small recessional moraines are interpreted to have been produced during short-lived, possibly annual re-advances of a grounded ice margin during overall retreat. This is the first time that these features have been shown to be part of the assemblage of landforms produced by tidewater glaciers on the Antarctic Peninsula. Glacier-terminus changes during the last four decades, mapped from LANDSAT satellite images, were analysed to determine whether the moraines were produced during recent still-stands or re-advances of Philippa Glacier and to further investigate the short-term (annual to decadal) variability in ice-marginal position in tidewater glacier systems. The asynchronous response of individual tidewater glaciers in Darbel Bay is interpreted to be controlled mainly by local topography rather than by glacier catchment-area size. C.L. Batchelor was in receipt of a Junior Research Fellowship from Newnham College, Cambridge during this work. K.A Hogan and R.D Larter are supported by the Polar Science for Planet Earth programme funded by the Natural Environment Research Council, U.K.